Portfolio Income: A Test of a Formula Plan - Dince, Robert R. (Journal of Financial and Quantitative Analysis, 1966)
One of the difficulties of evaluating formula plans by testing them in the light of past experience is the fact that there is no index of bond experience which simulates typical portfolio performance. Bond indices are stated in terms of yields with constant maturities, but the capital values of bonds vary according to their maturities given the same yield. Cottle and Whitman used elaborate techniques to make their bond portion of the total portfolio realistic, but were only partially successful. This writer also attempted to eliminate the problem of simulating the bond portfolio in a previous paper by assuming that the defensive portion of the portfolio was invested in a Savings and Loan account receiving the national average return. This procedure thus ignored the problem of bond maturities and variation in capital values due to changes in interest rates.